2012
DOI: 10.1007/s00330-012-2394-5
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the breast in patients with DCIS to exclude the presence of invasive disease

Abstract: It is important to determine invasion in breast DCIS. • MRI contrast medium uptake kinetics can help exclude the presence of invasion. • However, the positive predictive value for the presence of invasion is limited. • MRI features were more accurate at predicting invasion than mammographic features alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 43 publications
2
14
0
2
Order By: Relevance
“…Numerous studies have aimed to identify predictors of invasion once DCIS is diagnosed on preoperative biopsy. Previous studies have suggested the potential of mammographic and MR features [16,24,25] as well as histological features of DCIS [15,16,26] to predict the presence of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have aimed to identify predictors of invasion once DCIS is diagnosed on preoperative biopsy. Previous studies have suggested the potential of mammographic and MR features [16,24,25] as well as histological features of DCIS [15,16,26] to predict the presence of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the mean distance between the lesion and nipple was 2.7 mm shorter in the delay phase than the early phase, and prediction of NAC involvement was better when distance was measured in the delay rather than the early phases (Table ). Consistent with this findings, Wang et al reported patients with pure DCIS showed frequently persistent enhancement in the delayed phase (93.3% for DCIS vs 59.3% for invasive disease) and Deurloo et al demonstrated 60% of DCIS patients without invasion showed no enhancement or type I curve of late increasing enhancement. Another potential explanation was the clustered ring enhancement which could be detected in the mainly delayed phase of MRI and in many cases of DCIS presenting non‐mass‐like enhancement.…”
Section: Discussionmentioning
confidence: 54%
“…27 There were 125 with pure DCIS on core biopsy and 18 (14 %) had invasion on final histology. Suspicious enhancement on MRI was seen in 73 lesions, with a type 1 curve was seen in 12, type 2 in 19, and type 3 curve in 42.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 97%